Computer applications in drug discovery and development - Puratchikody, A. (Ayarivan), 1970-; Prabu, S. Lakshmana (Sakthivel Lakshmana), 1974-; Umamaheswari, A. (Appavoo), 1981- (IGI Global, 2019)
"This book examines how the use of computers for discovering and designing new drugs is becoming a central topic in modern molecular biology and medicinal chemistry. It also identifies promising compounds that might represent future solutions in critical areas of human health"--Provided by publisher.